2019
DOI: 10.1002/ece3.5079
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Pillars of Hercules: Understanding transoceanic migrations of seabirds throughout their breeding range

Abstract: Variability in long‐distance migration strategies is still poorly understood due to the fact that individuals are often tracked from a single colony/population. Transoceanic migrations of Scopoli's shearwaters ( Calonectris diomedea ) across the Strait of Gibraltar (SoG) have been tracked from several breeding colonies isolatedly, and factors related to the variability in phenological schedules among different populations remain, therefore, not well‐understood. Using light‐level geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The Strait of Gibraltar is an important landmark for migratory animals not only because it defines the limits between the Atlantic Ocean and the Mediterranean Sea, but also because it is frequently used to study the migratory passage and phenology of seabirds (Ramos 2019), including European Storm Petrels (Hashmi & Fliege 1994). Some of the tracked European Storm Petrels passed through the Strait of Gibraltar more than once at the beginning and/or at the end of the non‐breeding period.…”
Section: Methodsmentioning
confidence: 99%
“…The Strait of Gibraltar is an important landmark for migratory animals not only because it defines the limits between the Atlantic Ocean and the Mediterranean Sea, but also because it is frequently used to study the migratory passage and phenology of seabirds (Ramos 2019), including European Storm Petrels (Hashmi & Fliege 1994). Some of the tracked European Storm Petrels passed through the Strait of Gibraltar more than once at the beginning and/or at the end of the non‐breeding period.…”
Section: Methodsmentioning
confidence: 99%
“…In our example with these three phylogenetically close species that share nonbreeding areas, we found that the Cape Verde shearwater, the species with the most restricted breeding and nonbreeding distributions, had consistently higher inclusiveness values, The relationship with longitude, although not significant, might suggest a west-to-east decline in inclusiveness values. Birds breeding in the easternmost colonies of the Mediterranean used the northernmost nonbreeding areas preferentially (Ramos, 2019), which made their use of the southernmost nonbreeding locations less likely.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship with longitude, although not significant, might suggest a west‐to‐east decline in inclusiveness values. Birds breeding in the easternmost colonies of the Mediterranean used the northernmost nonbreeding areas preferentially (Ramos, 2019), which made their use of the southernmost nonbreeding locations less likely. Thus, they were not good in representing the entire nonbreeding distribution of the species, although necessary for the complete knowledge of the wintering grounds of the species.…”
Section: Discussionmentioning
confidence: 99%
“…In a still unexplained way, the birds overwintering over the Southwest Indian Ridge did not exhibit such synchronicity in their cycle of at-sea activity. Among seabirds, the influence of the moon phase on at-sea activity appears poorly marked for some species (Scopoli's shearwaters Calonectris diomedea (Ramos 2019); Bulwer's petrel Bulweria bulwerii (Dias et al 2016)), while clearly evidenced in others (e.g. Yamamoto et al 2008, Mackley et al 2011, Pinet et al 2011.…”
Section: The Inter-breeding Periodmentioning
confidence: 99%